Talking until nightfall : remembering Jewish Salonica 1941-44 - Matarasso, Isaak 1892-1958 (Bloomsbury Continuum, 2020)
An urgent conversation -- Early years, late reflections -- ...And yet not all died... -- From the Salonica Ghetto -- During your lifetime and during your days -- Listening to the witnesses